2005
DOI: 10.1044/1059-0889(2005/019)
|View full text |Cite
|
Sign up to set email alerts
|

The "Hearing Aid Effect" 2005

Abstract: The findings have implications for counseling potential users who are reluctant to try hearing aids for cosmetic reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 4 publications
0
8
1
Order By: Relevance
“…Although previous studies have shown conventional in the ear (ITE) models have the lowest visibility rating, and are therefore preferred, among hearing aid styles (Johnson et al., 2005), our findings revealed DTC devices with the ITE style were rated among the least cosmetically appealing. This can be attributed, in part, to the fact that conventional ITE hearing aids are molded to individual wearers’ ears and are thus less obtrusive than the noncustomised style that DTC devices necessarily adopt.…”
Section: Discussioncontrasting
confidence: 76%
“…Although previous studies have shown conventional in the ear (ITE) models have the lowest visibility rating, and are therefore preferred, among hearing aid styles (Johnson et al., 2005), our findings revealed DTC devices with the ITE style were rated among the least cosmetically appealing. This can be attributed, in part, to the fact that conventional ITE hearing aids are molded to individual wearers’ ears and are thus less obtrusive than the noncustomised style that DTC devices necessarily adopt.…”
Section: Discussioncontrasting
confidence: 76%
“…Lacking a theoretical framework, the majority of the studies included in our review were based on a description of the stigmatic attitudes associated with hearing loss and hearing aids (Cienkowski & Pimentel, 2001;Doggett, Stein, & Gans, 1998;Foss, 2014;Gleitman, Goldstein, & Binnie, 1993;Hindhede, 2012;Johnson, Danhauer, & Edwards, 1982;Kelly-Campbell & Plexico, 2012;Kochkin, 1990Kochkin, , 1993Mulac, Danhauer, & Johnson, 1983;Southall, Jennings, & Gagne, 2011;Wallhagen, 2010), and they related almost exclusively to the cognitive aspect of stigma, that is, they described only the stereotypes associated with hearing loss and hearing aids. The most common stereotype associated with hearing aids was "old age" (e.g., hearing aids are for old people, make you look older; Cienkowski & Pimentel, 2001;Gleitman et al, 1993;Hindhede, 2012;Johnson et al, 1982;Kelly-Campbell & Plexico, 2012;Kochkin, 1990Kochkin, , 1993Mulac et al, 1983;Wallhagen, 2010). Other stereotypes reported in the studies included "less communicatively effective when wearing hearing aids" (Johnson et al, 1982;Mulac et al, 1983;Southall et al, 2011), "being deaf" (Hetu, 1996;Hindhede, 2012) "less sociable/friendly" (Doggett et al, 1998;Hindhede, 2012), "looking disabled," "weak," "feeble" (Kochkin, 1993), "comical," "embarrassing," "lonely," and "less confident" (Doggett et al, 1998).…”
Section: Conceptual Issuesmentioning
confidence: 99%
“…The most common stereotype associated with hearing aids was "old age" (e.g., hearing aids are for old people, make you look older; Cienkowski & Pimentel, 2001;Gleitman et al, 1993;Hindhede, 2012;Johnson et al, 1982;Kelly-Campbell & Plexico, 2012;Kochkin, 1990Kochkin, , 1993Mulac et al, 1983;Wallhagen, 2010). Other stereotypes reported in the studies included "less communicatively effective when wearing hearing aids" (Johnson et al, 1982;Mulac et al, 1983;Southall et al, 2011), "being deaf" (Hetu, 1996;Hindhede, 2012) "less sociable/friendly" (Doggett et al, 1998;Hindhede, 2012), "looking disabled," "weak," "feeble" (Kochkin, 1993), "comical," "embarrassing," "lonely," and "less confident" (Doggett et al, 1998).…”
Section: Conceptual Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The wavering sense of worth could be an example of an external attribute that the hearing impaired learners could be receiving from significant and generalised others on feedback towards hearing aids use. Johnson et al (2005), on hearing aid effect shows that despite the improved design and size of hearing aids, there is still stigma amongst some of the students who wear them making them feel different. Wolters et al (2012), further supports the findings by affirming that peer relationship at school is important as it impacts the level of self-esteem.…”
Section: The Influence Of Hearing Aid Use On Self-esteem Among Learne...mentioning
confidence: 99%